2013
DOI: 10.1021/la401300u
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Triggered Degelation Control of Gold Nanoparticle Embedded Peptide Organogels

Abstract: Further understanding of the interactions between nanoparticles (NPs) and biological molecules offers new possibilities in the applications of nanomedicine and nanodiagnostics. The properties of NPs, including size, shape, and surface functionality, play a decisive role in these interactions. Herein, we evaluated the influences of gold NPs (AuNPs) with different sizes (5-60 nm) and shapes (i.e., spherical, rod, and cage) on the self-assembly of diphenylalanine (Phe-Phe) dipeptides. We found that the size of Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…In addition, we confirmed the laser-triggered degelation of a gold NPs containing gel made of click-C 12 -Cyc (c = 40 g L -1 ) in DMF incorporating HAuCl 4 ⋅3H 2 O (molar ratio gelator:Au = 1:1). Finally, in agreement with previous studies, 64 the bulk gel with a 75 T gel of ca. 40 ºC collapsed after 35 min of green laser exposure (λ = 532 nm, 50 mW/cm 2 ) due to the photothermal properties of the Au NPs.…”
Section: Formation Of Gold Nanoparticles-containing Gelssupporting
confidence: 93%
“…In addition, we confirmed the laser-triggered degelation of a gold NPs containing gel made of click-C 12 -Cyc (c = 40 g L -1 ) in DMF incorporating HAuCl 4 ⋅3H 2 O (molar ratio gelator:Au = 1:1). Finally, in agreement with previous studies, 64 the bulk gel with a 75 T gel of ca. 40 ºC collapsed after 35 min of green laser exposure (λ = 532 nm, 50 mW/cm 2 ) due to the photothermal properties of the Au NPs.…”
Section: Formation Of Gold Nanoparticles-containing Gelssupporting
confidence: 93%
“…Sershen et al have demonstrated independent control of microfluidic valves using nanocomposite hydrogels containing gold nanoparticles . The hydrogel has been formed by poly( N ‐isopropylacrylamide) which exhibits reversible thermal phase changes.…”
Section: Gels Driven By Photothermal Effectmentioning
confidence: 99%
“…[ 34,35 ] Such a conversion provides very rapid and localized heating with high selectivity. Starting from this point, we envisaged that by combining a temperature-sensitive polymeric thin fi lm with a directional AuNR arrays having photothermal properties, we may drive and guide liquid motion at a controlled speed using light illumination ( Figure 4 a).…”
Section: Doi: 101002/admi201500226mentioning
confidence: 99%